Adolescents with congenital heart defects: a patient and parental perspective of genetic information and genetic risk. (27th January 2020) - Crawford, Christopher A.; Vujakovich, Courtney E.; Elmore, Lindsey; Fleming, Emily; Landis, Benjamin J.; Spoonamore, Katie G.; Ware, Stephanie M.
Abstract: Congenital heart defects (CHDs) occur in 8 of 1000 live-born children, making them common birth defects in the adolescent population. CHDs may have single gene, chromosomal, or multifactorial causes. Despite evidence that patients with CHD want information on heritability and genetics, no studies have investigated the interest or knowledge base in the adolescent population. This information is necessary as patients in adolescence take greater ownership of their health care and discuss reproductive risks with their physicians. The objectives of this survey-based study were to determine adolescents' recall of their own heart condition, to assess patient and parent perception of the genetic contribution to the adolescent's CHD, and to obtain information about the preferred method(s) for education. The results show that adolescent patients had good recall of their type of CHD. Less than half of adolescents and parents believed their CHD had a genetic basis or was heritable; however, adolescents with a positive family history of CHD were more likely to believe that their condition was genetic (p = 0.0005). The majority of patients were interested in receiving additional genetics education and preferred education in-person and in consultation with both parents and a physician. The adolescents who felt most competent to have discussions with their doctors regarding potential causes of their heart defect previously had a school science course which covered topics in genetics. These results provide insight into adolescents' perceptions and understanding about their CHD and genetic risk and may inform the creation and provision of additional genetic education.